Moral machines teaching robots right from wrong - Wallach, Wendell, 1946-; Allen, Colin (Oxford : Oxford University Press, 2009)
'Moral Machines' is the first book to examine the challenge of building artificial moral agents, probing deeply into the nature of human decision making and ethics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Robotics; Computers -- Social aspects; Computers -- Moral and ethical aspects